2009
DOI: 10.1007/s11605-008-0786-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of ERCP-Related Perforations: Outcomes of Single Institution in Korea

Abstract: Introduction The aim of this study was to analyze clinicoradiologic findings and treatment outcomes of patients with endoscopic retrograde cholangiopancreatography (ERCP)-related perforations. Between May 2003 and November 2007, 2,247 ERCP procedures with or without sphincterotomy were performed at Ajou University Medical Center, Suwon, Korea, and 20 perforations (0.89%) were identified. Discussion We retrospectively reviewed medical and surgical records of each patient. Of 18 patients, 11 patients (61.1%) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Because the retroperitoneal space is a closed cavity, the retroperitoneal inflammation that develops after ERCP-related duodenal perforation seldom spreads rapidly into the peritoneal space. We previously reported that free intra-abdominal air and scope-related perforations could be indicators for early surgery; however, that study compared only the frequency of various clinical factors between conservative management and surgery, and the number of patients enrolled was too small for analysis of post-treatment outcome according to the clinical variables [15]. In contrast, the current study, which extended our previous study, analyzed the post-treatment survival outcomes too.…”
Section: Discussionmentioning
confidence: 71%
“…Because the retroperitoneal space is a closed cavity, the retroperitoneal inflammation that develops after ERCP-related duodenal perforation seldom spreads rapidly into the peritoneal space. We previously reported that free intra-abdominal air and scope-related perforations could be indicators for early surgery; however, that study compared only the frequency of various clinical factors between conservative management and surgery, and the number of patients enrolled was too small for analysis of post-treatment outcome according to the clinical variables [15]. In contrast, the current study, which extended our previous study, analyzed the post-treatment survival outcomes too.…”
Section: Discussionmentioning
confidence: 71%
“…The immediate treatment for ERCP-related perforations affected its mortality [7, 8, 1012]. There was no unified guideline to manipulate.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to management of type II perforations is less clear. Most tend to seal spontaneously by 2-3 days, but 10–43% of patients may require surgical repair [ 10 , 15 , 29 ]. Radiographic findings that require surgery include retroperitoneal or peritoneal fluid on CT, which suggests continued bile leak from site of perforation, and are associated with worse prognosis, large contrast extravasation on ERCP or UGI, and possibly the presence of massive subcutaneous emphysema.…”
Section: Discussionmentioning
confidence: 99%